CORPORATE SOCIAL RESPONSIBILITY (CSR)DISCLOSURE AND THE IMPLICATIONS OFEARNING RESPONSE COEFFICIENT (ERC) - ., Rusdin (AdBispreneur, 2016)
ABSTRACTÂ Â One of the reasons is social management reporting for strategic reasons. Although it is not yet compulsory, but it can be said that almost all the companies listed on the Indonesian Stock Exchange already disclose information about CSR in its annual report in diverse levels. The purpose of the study is to examine the effect of the information of Corporate Social Responsibility disclosed in the companiesâ annual reports on the informativeness of earnings (measured by earning response coefficient, ERC). The study hypothesized that there is negative effect of CSR disclosures level on the ERC since the CSR disclosures provide investors more information which is not captured by the accounting earnings. The sample of the study consist of 135 annual reports 2013 and 2014 of the companies listed at the Indonesia Stock Exchange. The empirical results of the study show that the level of CSR disclosures has negative effect on the ERC as predicted. The results of the study indicate that investors assess the CSR information disclosed by the companies in their annual reports for their investment decision.Â Keywords : corporate social responsibility, disclosure, earnings response coefficientÂ Â Â PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN IMPLIKASINYA TERHADAP EARNING RESPONSE COEFFICIENT (ERC)Â ABSTRAKÂ Â Salah satu alasan manajemen melakukan pelaporan sosial adalah untuk alasan strategis. Meskipun belum bersifat wajib, tetapi dapat dikatakan bahwa hampir semua perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) sudah mengungkapkan informasi mengenai CSR dalam laporan tahunannya dalam kadar yang beragam. Tujuan dari penelitian ini adalah untuk menguji pengaruh informasi dari Corporate Social Responsibility (CSR) yang diungkapkan dalam laporan tahunan perusahaan terhadap keinformatifan laba yang diukur melalui koefisien respon laba (Earning Response Coefficient/ERC). Hipotesis penelitian ini bahwa terdapat pengaruh negatif tingkat pengungkapan CSR terhadap ERC,ketika investor mendapatkan informasi CSR yang diungkapkan oleh perusahaan dalam laporan tahunan untuk keputusan investasi mereka yang tidak direspon oleh laba akuntansi. Sampel penelitian ini terdiri dari 135 laporan tahunan 2013 dan 2014 dari perusahaan yang terdaftar di Bursa Efek Indonesia. Hasil empiris dari penelitian ini menunjukkan bahwa tingkat pengungkapan CSR memiliki efek negatif terhadap ERC seperti yang diperkirakan. Hasil penelitian menunjukkan bahwa investor menilai informasi CSR yang diungkapkan oleh perusahaan dalam laporan tahunan mereka untuk keputusan investasi mereka.